Foods and substances influencing (lucid) dreams - Biehl, Josua (International journal of dream research, 2022)
Research on how substances and foods influence dreams and lucid dreams (i.e. the dreamer knows that they are dreaming while dreaming) is still scarce. For the present study, 436 participants, mainly collected from communities with interest in dreaming and lucid dreams, completed an online questionnaire and answered questions about consumption of some daily foods and substances alongside with dream recall, lucid dream frequency and other dream-related items. For possible interactions, demographics and Big Five personality factors were also collected and partial correlations were calculated. Prominent findings of this mostly explorative study were: when corrected for openness to experiences as an interactive variable, vitamin intake still correlated significantly with lucid dream frequency, (p = 0.013, r = 0.121), but not with dream recall (p = 0.112, r = 0.078); However, when instead corrected for dream recall and age, vitamin intake did not significantly correlate with lucid dream frequency (p = 0.066, r = 0.090); this suggests, vitamin intake influences either dream recall or lucid dream frequency. Also, consumption of fruits correlated with dream recall (p = 0.10, r = 0.124), which might be due to vitamins. Eating fish correlated significantly with lucid dream frequency, after controlling for extraversion and age (p = 0.012, r = 0.121), which is discussed to occur probably due to effects of omega-3 fatty acids. Consumption of chili correlated significantly with recall of hypnagogia, when controlled for age and openness to experiences (p = 0.002, r = 0.154), which is discussed to occur probably due to effects of capsaicin. Smoking correlated significantly with nightmares, after controlling for sleep paralysis (p = 0.049, r = 0.096). Use of antidepressants correlated significantly with lucid dream frequency (p = 0.012, r = 0.122), but also with nightmare frequency, even after controlling for neuroticism (p = 0.000, r = 0.197), which could not be explained by lucid dream frequency. Other hypotheses about certain foods or substances influencing dream variables could not be confirmed or provided less evident results. Further research is suggested for testing more detailed hypotheses based on these findings.
Gesehen am 18.10.2022